Individual Investors' Attention to Accounting Information: Evidence from Online Financial Communities* - Lerman, Alina (Contemporary Accounting Research, 2020)
ABSTRACT Online financial communities provide a unique opportunity to directly examine individual investors' attention to accounting information on a large scale and in great detail. I analyze accounting‐related content in large samples of Yahoo! message board posts and StockTwits and find investors pay attention to a range of accounting information, fixating particularly on earnings, cash, and revenues. Consistent with the expectation that investors react to relevant information events, I find accounting‐related discussion elevated around the filings of earnings releases and 8‐K reports, but the reaction to periodic reports is confined to small firms. I also find investors expand their acquisition of accounting information and processing efforts in poor information environments. Greater attention to accounting information at earnings releases does not appear to be meaningfully associated with better information processing.